(untitled) (Journal of Tikapur Multiple Campus, 2025)
Poverty and inequality remain critical issues in Nepal despite significant poverty reduction over recent decades. Rural and urban poverty trends differ with rural poverty decreasing due to remittances and agricultural productivity, while urban poverty has risen due to migration pressures. This study examines the socio-economic determinants influencing poverty and inequality, focusing on regional differences and policy impacts. Utilizing data from four rounds of the Nepal Living Standards Survey (1995-2023), this study applies descriptive statistics and graphical analysis to assess poverty and inequality trends. Key metrics include the poverty headcount ratio, poverty gap, and Gini coefficient, analyzed across both rural and urban regions to identify distinct socio-economic drivers. Findings indicate a significant reduction in national poverty, primarily driven by remittances although urban poverty has intensified with rapid rural-to-urban migration. The poverty gap and Gini coefficient reveal that inequality remains higher in rural areas despite some improvements. This study highlights the need for region specific policies that address rural poverty drivers and urban challenges tied to migration and inadequate infrastructure. The study concludes that a dual policy approach—targeting rural development and urban poverty management—is necessary for sustainable poverty reduction in Nepal. Future research should further explore long-term impacts of remittances and urban focused poverty interventions.